(3OhQ GdESJKeGQ GdCLfHj GdeHGTQ aj GdJfejI GdGbJUGOjI(B. /s - (3GdLHhQj, YHO GdRQGb MeO MSjfs ((3YeGf(B: s (3OGQ GdMGeO ddfTQ h GdJhRjY(B, s, 2014)
(3jVe GdEWGQ GdfXQj ddESJKeGQ GdCLfHj GdeHGTQ hjYed Ydi JMdjd ChVGY GdESJKeGQ GdCLfHj GdeHGTQ aj GdHdOGf GdYQHjI h eDTQGJ Jbhjeg, hGbY GdESJKeGQ GdCLfHj GdeHGTQ aj EWGQ GdHjFI GdGbJUGOjI GdcdjI ddHdOGf GdYQHjI GdeNJGQI, bjGS CKQ GdGSJKeGQ GdGLfHj GdeHGTQ aj HYV GdeJZjQGJ GdEbJUGOjI GdcdjI aj GdHdOGf GdYQHjI GdNJGQI ddeOI (B1990-2005.s
(3GdeQGLY U(B.311 (3GdedGMb U(B.307s
Keywords: (3GdESJKeGQs; (3GdESJKeGQ GdCLfHj(B- (3GdHdOGf GdYQHjIs; (3GdJfejI GdEbJUGOjIs